Flp, a Fis‐like protein, contributes to the regulation of type III secretion and virulence processes in the phytopathogen Xanthomonas campestris pv. campestris. (14th May 2019) - Leng, Ming; Lu, Zhuo‐Jian; Qin, Zuo‐Shu; Qi, Yan‐Hua; Lu, Guang‐Tao; Tang, Ji‐Liang
Summary: The ability of the plant pathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on its ability to adapt quickly to the host environment during infection. Like most bacterial pathogens, Xcc has evolved complex regulatory networks that ensure expression and regulation of their virulence genes. Here, we describe the identification and characterization of a Fis‐like protein (named Flp), which plays an important role in virulence and type III secretion system (T3SS) gene expression in Xcc . Deletion of flp caused reduced virulence and hypersensitive response (HR) induction of Xcc and alterations in stress tolerance. Global transcriptome analyses revealed the Flp had a broad regulatory role and that most T3SS HR and pathogenicity ( hrp ) genes were down‐regulated in the flp mutant. β ‐glucuronidase activity assays implied that Flp regulates the expression of hrp genesvia controlling the expression of hrpX . More assays confirmed that Flp binds to the promoter of hrpX and affected the transcription of hrpX directly. Interestingly, the constitutive expression of hrpX in the flp mutant restored the HR phenotype but not full virulence. Taken together, the findings describe the unrecognized regulatory role of Flp protein that controls hrp gene expression and pathogenesis in Xcc .